Guided Inquiry Learning Model to Improve Students Science Literacy Skills and Learning Outcomes - Nissa, Aliefiya Choirun; Mu'minin, Ali Amirul; Ardhana, Ivan Ashif (Universitas Negeri Malang, 2024)
Students science literacy skills and learning outcomes tend to be low in chemical equilibrium material. One of the influence factors is the use of not exactly learning models. An alternative that can be done is using the guided inquiry learning model. This research aims to determine the effect of the guided inquiry learning model to improve student science literacy skills and learning outcomes chemical equilibrium. The research design was used Quasi-Experimental tipe Nonequivalent Control Only Group Design. The experimental class use the guided inquiry learning model meanwhile the control class use the conventional learning model. The data analysis technique was used independent sample t-test and manova test. The results of hypothesis test used independent sample t-test on science literacy skills of 0,000